Review of Performance Indicators in TPM and New Approach to Calculating MTTR - Mikolaj SZYNKOWSKI; Krzysztof JOZWIK; Zbigniew WISNIEWSKI (Communications of International Proceedings, 2021)
The Total Productive Maintenance methodology, which allows organizations to increase the efficiency of a manufacturing company, is discussed. The evolution of the process is shown and a preferred manner of implementation, controlled with specific performance indicators, is recommended. Methods of calculating the indicators are considered complete with recommendations for their application. New approach to determine the Mean Time To Repair indicator, is being presented. The paper provides examples of different organisations and machine parks for which specified approaches for calculating MTTR, are beneficial.
Keywords: Total Productive Maintenance; TPM; OEE; MTBF; MTTR.